ISLAM DAN SENI (Institut Agama Islam Negeri (IAIN) Palu, 2007)
Islam is a universal religion that regulatesÂ relationship not only between mankind and God, between mankind and mankind but also between mankind and their soroundings.Â It is within this context that moral teaching of the Qurâan and of prophetâs tradisition often becomeÂ references ofÂ a Muslimâs deed, including his or her art expression. This article deals with Islam and art. In other words, to which extant does Islam permit a Muslim to perform an art.Kata Kunci : Islam, etika kesenian, seni estetika